2018
DOI: 10.1021/acsami.8b17474
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Morphology on Iron Oxide Nanoparticles-Induced Inflammasome Activation in Macrophages

Abstract: Inflammasomes, a critical component of the innate immune system, mediate much of the inflammatory response manifested by engineered nanomaterials. Iron oxide nanoparticles (IONPs), a type of nanoparticles that have gained widespread acceptance in preclinical and clinical settings, are known to induce inflammasome activation, but how morphology affects the inflammasome-activating property of IONPs has not been addressed. In this report, we have synthesized four morphologically distinct IONPs having the same asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 55 publications
0
37
0
Order By: Relevance
“…Zn and Fe were quantitated with ICP-MS after dissolving them in boiling HNO 3 for 1 h. Fe 3 O 4 was synthesized by following the previous publication. [46] Cell Lines and Culture Conditions: ES-2, BT-549, and BxPC3 were grown in RPMI 1640 medium with 10% FBS. MDA-MB-231, MIA PaCa-2, A549, Hela, APRE-19, and H1299 were grown in DMEM medium with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Zn and Fe were quantitated with ICP-MS after dissolving them in boiling HNO 3 for 1 h. Fe 3 O 4 was synthesized by following the previous publication. [46] Cell Lines and Culture Conditions: ES-2, BT-549, and BxPC3 were grown in RPMI 1640 medium with 10% FBS. MDA-MB-231, MIA PaCa-2, A549, Hela, APRE-19, and H1299 were grown in DMEM medium with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, using 4 different shapes of iron oxide nanoparticles (IONPs), the authors have demonstrated that exposure to the ocatpod and plate-shaped IONPs was associated with increased release of IL-1β release and more cell pyroptosis when compared to the sphere and cube nanoparticles. It has been also found in the same study that activation of the inflammasome by the iron oxide nanoparticles was only partially mediated by NLRP3 (51). Such findings indicate that the same ENMs may induce activation of the inflammasome through multiple receptors/biological targets.…”
Section: Interaction With and Activation Of The Complement Systemmentioning
confidence: 66%
“…Our in vitro experiment showed that SPION significantly increased oxidative stress damage to overactivate autophagy and endoplasmic reticulum stress, eventually resulting in cardiomyocyte apoptosis 12 . Furthermore, SPION could elicit IL‐1βrelease and pyroptosis in macrophages, especially with the octapod and plate morphology 16 . Notably, it has been recently reported that sorafenib or cisplatin assembled into nano‐devices containing SPION, which are phagocytized by tumour cells and degraded into free divalent iron to accelerate Fenton reaction, leading to the lipid peroxidation burst to promote ferroptosis of tumour cells 17,18 …”
Section: Introductionmentioning
confidence: 85%